Perancangan User Experience Aplikasi Web Pelaporan Tempat Pembuangan Sampah Reduce, Reuse, Recycle Dinas Lingkungan Hidup Kota Batu menggunakan Metode Human Centered Design - Hendrikus Dimas Samara; Hanifah Muslimah Az-Zahra; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The reduce,reuce,recycle (TPS3R) landfill is an important element in terms of waste management in Batu City which is managed by the Batu City Environment Service (DLH). it aims to help with TPS3R reporting problems by designing a TPS3R waste reporting system so that it can ease the workload of DLH staff in Batu City. System design is carried out using the Human Centered Design method which prioritizes user needs in designing the system. from this research in the form of wireframes, mockups, and prototypes that describe the original function of the system. efficiency, as well as user satisfaction in trying the system prototype. The prototype that has been made is tested to measure whether the system design made is acceptable to users. Testing was carried out using usability testing to 5 respondents, the aspects tested were effectiveness, efficiency, and user satisfaction in trying the system prototype. The results obtained in the test are an effectiveness value of 91.42%, an efficiency value of 0.1271 goals/second, and a user satisfaction value of 80 points which gets a B value and is categorized as Good.